Convergence and Integration: Funds, Functions and Functionaries of Government Programs - CGIAR Research Program on Climate Change, Agriculture and Food Security; BAIF Development Research Foundation (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The convergence of funds and efforts of stakeholders is playing a crucial role in anchoring climate-resilient agricultural practices in the project states of Madhya Pradesh, Uttar Pradesh, and Bihar of India.